Islamic algorithms: online influence in the Muslim metaverse - Bunt, Gary R. (Bloomsbury Academic, 2024)
This book examines how Islam is digitally mediated at a time of technological change, enhanced digital literacy and proactive engagement in Islamic online content by authorities and influencers. What is the impact of this on societies, believers and understandings of Islam? Islamic Algorithms provides a thorough exploration of Cyber Islamic Environments (CIEs) through representations of significant historical and religious influences across contexts and diversities. This ranges from jinn and angels through to contemporary influencers. Gary R. Bunt raises issues of how digital content is embedded in contemporary understandings of Islam and their dissemination. Bunt shows how the interpretation of pivotal figures in Islam - including Muhammad and his family, scholars and imams - can be informed by new generations of digital influences, such as apps and social networking, which have become primary sources of information for many Muslims globally